Lipid Profile and Liver Histochemistry in Animal Models Exposed to Cigarette Smoke - Omotoso, Gabriel Olaiya; Enaibe, Bernard U; Akinola, Oluwole Busayo; Kadir, R Eniola; Akinlolu, Adelaja A; Oyewopo, Adeoye Oyetunji; Olawuyi, Solomon Toluwase; Adebayo, Joseph Oluwatope; Apalowo, , Olanrewaju Samuel; Sofoluwe, Adeyemi Victor (Journal of Basic & Applied Sciences, 2012)
Cigarette smoke is known to be an important predisposing factor to many diseased conditions, such as cardiovascular diseases, liver disease, atherosclerosis and other metabolic disorders. The aim of this study was to examine the effects of exposure to smoke from burnt cotton wool and cigarette on plasma lipids, liver biochemistry and histology, in adult Wistar rats. The animals were divided into three groups of Control A: exposed to fresh atmospheric air; Group B: exposed to cotton wool smoke; and, Group C, exposed to cigarette smoke; and the experiment lasted for 35 days. The animals exposed to cigarette smoke and cotton wool smoke showed higher values of low density lipoprotein (LDL), and lower values of high density lipoprotein (HDL) compared to the control. The observation of the micro architecture and enzymes of the liver tissue revealed reduction in the number and size of liver cells, numerous fibrous tissues, elevated liver transaminases and reduction in endogenous anti-oxidants, with evidence of fatty degeneration, in animals exposed to cigarette smoke compared to those exposed to cotton wool smoke and fresh atmospheric air. Cigarette smoke caused accumulation of lipids in the liver cells, with evidence of on-going necrosis and fibrosis, which indicated the presence of non-alcoholic fatty liver disease.